Judicial territorial competence in teleworking cases in light of the doctrine of the Supreme Court - Romero Burillo, Ana María (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
This study examines one of the “grey areas” arising from the practical application of Law 10/2021, of July 9, on Remote Work; specifically, the determination of territorial jurisdiction in the event of a conflict. The research addresses the controversy generated by the locative element of teleworking, which has resulted in conflicting judicial interpretations. It further analyses the diverse criteria adopted in court rulings and evaluates the Supreme Court’s jurisprudence on the issue.